Morphological characterization and epidemiological studies of summer squash (Cucurbita pepo) powdery mildew - BHARMERA, POOJA; GUPTA, S K; PARSAD, DURGA; SHARMA, MONICA (The Indian Journal of Agricultural Sciences, 2021)
Samples of powdery mildew of summer squash (Cucurbita pepo L.) collected from Solan, Shimla, Hamirpur and Kinnaur districts of Himachal Pradesh during 2017-18 revealed the presence of anamorphs, whereas the cool and dry temperate region of district Kinnaur showed the occurrence of both teleomorphic and anamorphic stages of powdery mildew on summer squash. Present studies constitute the first report of cleistothecial occurrence on summer squash under Indian conditions. Based on anamorphic characters like ellipsoidal conidia, presence of fibrosin bodies and germinating conidia produced both simple and forked germ tubes without appressorium and teleomorphic characters like cleistothecia with myceloid appendages, single ascus with eight ascospores the associated pathogen was identified as Sphaerotheca fuliginea (Schlecht.) Pollaci. Maximum conidial germination was observed at 25° temperature and 100% relative humidity. The development of powdery mildew disease was significantly favored at moderate temperature coupled with high relative humidity and cumulative rainfall.